Políticas públicas de proteção do emprego e da renda : um olhar à luz do princípio da vedação ao retrocesso social - Veiga, Fabiano de Aragão (2023)
This research aims to analyze the public policies implemented with the purpose of protecting employment and income, studying the extent to which they have achieved the intended objectives, with the reduction of economic and social inequalities, and, consequently, with the preservation and appreciation of the dignity of the human person, in light of the principle of prohibition of social regression and constitutional values. The year 1988 was established as a timeframe, and the Federal Constitution of 1988 as a legal framework. As a legal framework, legislative initiatives in the labor area will be analyzed. It consists of an introduction, three chapters and a conclusion. The first chapter is dedicated to the study of public policies, concept, phases and characterization, the relationship with fundamental rights, as well as the fundamental right of job and income protection. In the second chapter, the impacts of neoliberalism on public labor policies were studied, focusing on the crisis of fundamental social rights, in addition to the legal content of the principle of prohibition of social retrogression. The third chapter, in turn, deals with the concrete analysis of public policies in labor relations, specifically in the creation (and preservation) of employment and income. Initially, it addresses the role of the STF in public policies in labor relations, the deconstitutionalization of Labor Law, deregulation and flexibility of labor legislation, based on the movement away from Labor Law, through concrete legislative measures, with precariousness as its guide of human labor, as a movement resulting from the neoliberal model. Official data on the level of employability in Brazil were analyzed, having as a framework, above all, the period before and after the Labor Reform, and, finally, the compatibility of the measures with the labor management model established by CRFB/88, to light of the content of the principle of the prohibition of retrogression.